2005
DOI: 10.1080/13651820510028846
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency ablation versus surgical resection for single nodule hepatocellular carcinoma: Long‐term outcomes

Abstract: Although the groups were not truly comparable, this retrospective study suggests that RFA may offer similar long-term results to surgical resection for single nodule HCC when combined with multimodal treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(38 citation statements)
references
References 20 publications
3
35
0
Order By: Relevance
“…5). Similar findings were also noted in other reports [12,13,14,15,16,17,18]. Based on these, resection is recommended for cases with 3 or fewer tumors 3 cm or smaller in which resection is readily applicable with regard to the liver function and localization, and only a small amount of liver tissue is sacrificed, but RFA is recommended for tumors located in a deep region, when the liver function capacity is graded as Child-Pugh B, or the tumor extends over the bilateral lobes.…”
Section: Outcomes and Survival Following Rfa: Comparison With Those Asupporting
confidence: 82%
“…5). Similar findings were also noted in other reports [12,13,14,15,16,17,18]. Based on these, resection is recommended for cases with 3 or fewer tumors 3 cm or smaller in which resection is readily applicable with regard to the liver function and localization, and only a small amount of liver tissue is sacrificed, but RFA is recommended for tumors located in a deep region, when the liver function capacity is graded as Child-Pugh B, or the tumor extends over the bilateral lobes.…”
Section: Outcomes and Survival Following Rfa: Comparison With Those Asupporting
confidence: 82%
“…18,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] All studies were retrospective except for three which were prospective, 27,30,34 including two randomized trials. 30,34 Some studies reported specific data for solitary 18,22,24,26,28,32,34,36,39,40 or small tumours. 18,22,26,[30][31][32][34][35][36]40 A study based on a theoretical mathematical analysis using the Markov modelling to simulate a randomized trial of RFA and HR for HCC less than 5 cm was also retrieved and discussed, but its numeric data were not included.…”
Section: Resultsmentioning
confidence: 99%
“…Eight articles included patients outside the Milan criteria in their comparison between RFA (797 patients) and resection (712 patients) 24,44,48,49,52,58,60,61 . Because of larger numbers and sizes of tumours, four of the studies combined RFA with TACE 48,52,60,61 .…”
Section: Radiofrequency Ablation Versus Resection Outside Milan Criteriamentioning
confidence: 99%